TEST STUDENT-NEWMAN-KEULS BOOTSTRAP: PROPOSAL, EVALUATION, ANDA APPLICATION PRODUCTIVITY DATA OF SOURSOP - GONÇALVES, Bruna de Oliveira; RAMOS, Patrícia de Siqueira; AVELAR, Fabricio Goecking (Brazilian Journal of Biometrics, 2015)
The aim of this work was to propose a modication of the SNK test for multiple comparisons using bootstrap resampling (SNKB) and evaluate the performance of the two versions of the test. The performance was evaluated by experimentwise error rates and power using a Monte Carlo simulation study considering normal and non-normal residuals. Both tests were exact under H0 and normality.